After the bazooka a bonanza from heaven: "Helicopter money" now? - Ansgar Belke (Research On Money in the Economy (ROME), 2018)
Helicopter money has once been proposed as a theoretical thought experiment by Milton Friedman in order to elucidate the effect of money injections into the macroeconomy over time. However, some Euro area member states nowadays consider helicopter money, i.e. permanent Quantitative Easing (QE), as a permanent ingredient of future EMU governance. We set helicopter money apart from QE monetary policy measures and also distinguish it from a traditional fiscal stimulus. We then deal with and critically assess further developments of the helicopter money idea à la Bernanke und Buiter. Furthermore, the paper then comes up with three practical variants of helicopter money, basically available for the European Central Bank. Taking this as a starting point, the pros and cons of helicopter money and its closely defined implementation conditions are discussed. Finally, we derive some implications of helicopter money implementation for the monetary system as a whole.
Keywords: E52; E58; E63; 330; economic stimulus programmes; full reserve banking; helicopter money; interest rate; joint analysis of fiscal and monetary policy; Quantitative Easing